Early, maturing and high yielding Rainfed upland rice variety, CRAM 4 (ART15-16-12-3-1-B-1-B-3-1), released in Cote d'Ivoire - CGIAR Research Program on Rice (2021)
An early maturing and high yielding rice variety, CRAM 4(ART15-16-12-3-1-B-1-B-3-1), was released in 2021 in Cote d'Ivoire for rainfed upland systems.